Remote Control Target Tracking Using GPS / INS-IMU. Issue 1 (February 2021) - Syafruddin, R; Ramady, Givy Devira; Herawati, YS; Mahardika, Andrew Ghea; Lestari, Ninik Sri; Hidayat, Rahmad
Abstract: Background of this research is the need for the remote control to direct a bullet to a known target in advance of the coordinates, with an initial velocity, and initial momentum of the bullet flying the farthest possible. Method of developing remote control target tracking uses GPS sensor devices. By using a radio receiver and CPU, GPS data can be received where there are some data that can be used directly and some are processed first to be used, including position data directly sent to the base as control host and plotted on maps, altitude data or altitude is directly used to control the altitude, the direction of the bullet is calculated using the position data every second from the GPS and compared with the GPS direction data attached to the bullet, used to correct the direction of the bullet, where the data that is executed is the delta heading for calculation with the heading GPS. Remote control target tracking using GPS worked fine, according to the target coordinates as reference. Emphasis on research is how to calculate the real-time server heading, and compare it with the heading from a compass sensor mounted on the bullet.